Radical Collections Re-examining the roots of collections, practices and information professions - Landes, Jordan; Espley, Richard (University of London Press, 2018)
Do archivists 'curate' history? And to what extent are our librarians the gatekeepers of knowledge? Libraries and archives have a long and rich history of compiling 'radical collections'- from Klanwatch Project in the States to the R. D. Laing Archive in Glasgow, but a re-examination of the information professions and all aspects of managing those collections is long overdue. This new book shines a light on pressing topical issues within library and information services (LIS)- to encompass selection, appraisal and accession, through to organisation and classification, and including promotion and use. Will libraries survive as victims of neoliberal marketization? Do we have a responsibility to collect and document 'white hate' in the era of Trump? And how can a predominantly white (96.7%) LIS workforce effectively collect and tell POC histories?